Giant Whip Scorpion Mastigoproctus giganteus giganteus (Lucas, 1835) (Arachnida: Thelyphonida (=Uropygi): Thelyphonidae) - William H. Kern; Ralph E. Mitchell (EDIS)
To encounter a giant whip scorpion for the first time can be an alarming experience! What seems like a miniature monster from a horror movie is really a fairly benign creature. While called a scorpion, this arachnid has neither the venom-filled stinger found in scorpions nor the venomous bite found in some spiders. This 4-page fact sheet was written by W.H. Kern Jr. and R.E. Mitchell and published by the UF Department of Entomology and Nematology, May 2011.